An investigation on the relationship between Service Quality and Customer Loyalty: A mediating role of Customer Satisfaction - Leninkumar, Vithya (Archives of Business Research, 2017)
Post war developments in Northern Province of Sri Lanka paved a way for hyper-competition in the market place among the already existing and the new banks where the former focuses on retaining the existing customers and the latter on attracting new customers. Such an intense competition emphasizes the need for identification of determinants of customer loyalty. Thus, the current study attempts to fill the empirical gap that exists especially in the Sri Lankan context. The study was conducted in a Commercial Bank setting and the hypotheses were developed in order to find out the relationship between the constructs. The population consisted of customers of Commercial Banks in the Northern Province of Sri Lanka and the sample of 300 respondents were selected. The data were analyzed using SPSS version 21.0 and SmartPls version 3.0. The findings revealed a positive, significant direct relationship between the service quality and customer satisfaction; customer satisfaction and customer loyalty and service quality and customer loyalty. Further, mediating effect of customer satisfaction between service quality and customer loyalty was proved. The paper discusses both Theoretical and practical implications.